The Evaluating Customer Relationship Marketing Strategy on Customer Retention at DMKR Fashion Company - Husaini, Galih Rashif; Lubis, Muharman; Andiharsa Sih Setiarto, Rahardian; Fauzan, Ratandi (Electronic Integrated Computer Algorithm Journal, 2026)
Building and maintaining strong relationships with customers is essential for business sustainability, especially in an increasingly competitive market where customer loyalty can shift easily. Customer Relationship Management (CRM) has become an important strategic approach that allows companies to manage customer data, strengthen communication, and improve customer experiences. CRM also supports public relations activities by enhancing trust and long-term engagement. During the COVID-19 pandemic, business owners at Dakar, a local MSME in the batik fashion industry, faced significant uncertainty and were required to adapt quickly to changing customer needs and digital consumption patterns. Despite this challenge, the company continued to identify opportunities to strengthen customer loyalty and retention through various CRM-based strategies. This study examines how Dakar implements CRM and evaluates its impact on customer retention using qualitative methods supported by sales and customer behavior data. The results show that CRM contributes to better understanding customer preferences, improving service quality, and encouraging repeat purchases. Furthermore, CRM helps Dakar build emotional bonds with customers through product personalization, social engagement, and the integration of digital platforms. Overall, CRM plays a crucial role in supporting business resilience and customer loyalty in the post-pandemic era.